Decision Tree and Ordinal Logistic Regression Methods for Maintaining University Sutainability - Siew Chin Teoh; Mohammed Syazwan Mohd Shokri; Rosshairy Abd. Rahman (International Journal of Supply Chain Management, 2019)
Recently, there are lots of cases regarding the use of fake account and cyberbullying. The irresponsible attitude is badly affecting the motivation of individual who being attacked and ruining the reputation of organization involved. This study is conducted among university students that aims to determine the factors of choosing fake account as a medium to raise an issue and to identify the impact of cyberbullying towards university’s reputation. About 380 samples were taken from undergraduate and postgraduate students. The data was analyzed using Decision Tree and Ordinal Logistic Regression (ORD) methods. The results show that there are students who have experienced cyberbullying or cyber victimization, which caused by the lack of parental support. The analysis from ORD method shows that fake account could affect university’s reputation. Hence, this research hopefully capable to create awareness among university students and help them to proudly present their university’s great name throughout the world. This is important to ensure the sustainability of community and university.